PRODUKTIVITAS BUDIDAYA JAMUR TIRAM MELALUI SISTEM PENYIRAMAN OTOMATIS BERBASIS IOT - Imam Permana; Anwar Rifa'i; Abdullah Kafabihi; Muhammad Darus Alfahrizi (Universitas Mataram, 2026)
Oyster mushroom cultivation in Rumpin District, Bogor Regency, faces significant productivity constraints due to unstable temperatures and humidity in the mushroom houses (kumbung). Management that still relies on manual methods causes extreme environmental fluctuations. This condition directly leads to inconsistent harvests and a high susceptibility to failure. As a result, the partner farmers' income improvement is hindered. This community service program aims to design and implement an automatic watering system based on the Internet of Things (IoT) to maintain environmental stability in the mushroom houses. The activity methods included the design and implementation of an IoT-based automatic watering system. This system utilizes a DHT22 sensor, a NodeMCU microcontroller, and a water pump actuator, accompanied by intensive training and mentoring for partner farmers. The results of this technology implementation show significant changes. The system is able to maintain stable humidity in the mushroom house within the optimal range of 60-80% automatically. This has a direct impact on an 18% increase in average monthly harvest yields. Furthermore, the baglog failure rate decreased dramatically by 60%, and work time efficiency increased by over 90% as the manual watering process was replaced. In conclusion, the utilization of IoT technology is proven to be an effective solution for increasing the productivity and efficiency of oyster mushroom cultivation.